Effect of temperature on the wear properties of alloy steel under jatropha curcas biodiesel - Shaufe, N. A.; Maleque, Md. Abdul; Saleh, Abu Ahmed; Paruka, Perowansa (Trans Tech Publications, Switzerland, 2015)

(untitled)
This paper presents the effect of Jatropha curcas biodiesel on the wear properties of mild steel, which was coated by preplacement of TiC particulate and melting it using a conventional TIG torch arc heat source. The aim of the study is to investigate the wear behaviour of surface modified AISI 4340 steel and the uncoated AISI 4340 steel which were performed using CSM tribometer at four different temperatures viz., 100 °C, 120 °C, 140 °C, and 160 °C, with the presence of jatropha biodiesel. At the end of the tests, wear characteristics was investigated by weight loss measurements and changes of the exposed metal surface. Surface morphology was examined by scanning electron microscope and surface profilometry. EDX analysis was performed on the samples’ surface. Results showed that wear of alloy steel increases with increasing temperature. TiC coated alloy steel showed improved wear resistance as this alloy steel demonstrated lower wear volume loss as compared to the uncoated steel in presence of jatropha biodiesel at higher temperature